Internal and external stimuli of online shopping cart abandonment and decision to buy from a land-based retailer - Wang, Siqi (2022)
The growth of e-commerce has disrupted traditional forms of consumption, and consumer shopping activity is rapidly digitalizing. Scholars have conducted a plethora of studies on online shopping behavior; however, a phenomenon that has surprisingly received less attention in the consumer behavior literature is "non-purchase behavior", particularly online shopping cart abandonment (OSCA). Though OSCA may be the topmost frustrating outcome for e-retailers in generating sales, the stimuli factors leading to this behavior and the determinants of the decision to buy from a land-based retailer (DBLR) remain relatively unexplored. To fill the gaps in the literature, this study aimed to identify the determinants of OSCA and DBLR among Mainland China consumers. First, the cognition-affect-behavior (C-A-B) model and buyer behavior theory were employed to explain the causal patterns of factors that stimulate online non-purchasing behavior. Specifically, the effects of consumers' cognitive factors (i.e., internal stimuli - attribute conflicts, self-efficacy, and interpersonal conflicts; and external stimulus - total costs) and affective states (i.e., emotional ambivalence, wait for lower price) on output behaviors (i.e., hesitation at checkout, OSCA, and DBLR) were evaluated. Next, the mediating role of hesitation at checkout in the research framework was explored. Finally, expectancy disconfirmation theory was adopted to test the moderating role of perception factors (i.e., perceived transaction inconvenience, perceived risk). Data from 883 questionnaires were collected through an online platform (i.e., Wenjuanxing). Purposive sampling was used to ensure that the respondents were Mainland China consumers with experience in online shopping. Subsequently, the data were analyzed using partial least squares structural equation modelling (PLS-SEM). Several significant findings were found, as follows: i) internal stimuli (i.e., attribute conflicts, self-efficacy, and interpersonal conflicts) positively influence emotional ambivalence; ii) the external stimulus, total costs, positively influences consumers' emotional ambivalence; iii) total costs positively influences the wait for lower price; iv) affective states (i.e., emotional ambivalence, wait for lower price) positively influence hesitation at checkout; v) hesitation at checkout mediates the relationship between affective states (i.e., emotional ambivalence, wait for lower price) and OSCA; and vi) perception factors (i.e., perceived transaction inconvenience, perceived risk) strengthen the relationship between emotional ambivalence and hesitation at checkout. This study provides theoretical contributions and managerial insights for scholars and e-retailers.